2014
DOI: 10.1590/s0100-204x2014001200002
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil replacement by soybean oil in the diet of fat snook juveniles

Abstract: -The objective of this work was to evaluate fish oil replacement by soybean oil in diets, as for the effects on the performance and body composition of juveniles of fat snook (Centropomus parallelus). The experiment was carried out in a randomized block design, with three treatments (lipid sources) and six replicates, in a 60-day period. Fat snook juveniles (24.17±0.28g) were distributed in 18 experimental tanks of 200 L each, equipped with aeration and heating systems, under continuous water renovation (800% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the present study, channel catfish showed no difference in WG and FCR ( p > .05), when the fish were fed 60 g/kg fish oil or soybean oil (OFO‐0 and OSO‐0) (Table ). Similarly, in hybrid sturgeon, Acipenser baeri Brandt × Acipenser schrenckii Brandt (Liu et al, ); darkbarbel catfish, Pelteobagrus vachelli (Jiang et al, ); and fat snook, Centropomus parallelus (Bendhack, Baldan, & Fabregat, ), the complete substitution of fish oil with soybean oil also did not significantly affect the growth performance of these fish. The role of dietary lipid is to provide energy and meet the needs for essential fatty acid.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, channel catfish showed no difference in WG and FCR ( p > .05), when the fish were fed 60 g/kg fish oil or soybean oil (OFO‐0 and OSO‐0) (Table ). Similarly, in hybrid sturgeon, Acipenser baeri Brandt × Acipenser schrenckii Brandt (Liu et al, ); darkbarbel catfish, Pelteobagrus vachelli (Jiang et al, ); and fat snook, Centropomus parallelus (Bendhack, Baldan, & Fabregat, ), the complete substitution of fish oil with soybean oil also did not significantly affect the growth performance of these fish. The role of dietary lipid is to provide energy and meet the needs for essential fatty acid.…”
Section: Discussionmentioning
confidence: 97%